Determinants for using visible reserves in German banks: an empirical study - Sven Bornemann; Susanne Homölle; Carsten Hubensack; Thomas Kick; Andreas Pfingsten (Deutsche Bundesbank, 2009)
The German Commercial Code (HGB) allows banks to build visible reserves for general banking risks according to section 340g HGB. These GBR reserves may, in addition to their risk provisioning function, be used to enhance capital endowment, for internal financing, signaling or earnings management purposes. We analyze financial statements of German banks for the period from 1995 through 2007 to reveal specific patterns in the use of GBR reserves. Our empirical investigation is based on a large, unbalanced panel of German banks including 32,023 bank-year observations. We see an increase in the use of GBR reserves over time. Furthermore, we can say that GBR reserves are primarily used by large banks, banks with comparatively low regulatory capital endowment, as well as those with lower risks. Furthermore, GBR reserves are used by fairly profitable banks, those reporting according to international financial reporting standards in addition to HGB, and banks which are not thrifts or cooperative banks. Finally, we find that banks which make use of hidden reserves according to section 340f HGB also tend to hold GBR reserves. We explain our findings with regulatory factors and existing information asymmetries as well as banks' size and ownership structure.
Keywords: G21; G32; M41; 330; Bank regulation; informational asymmetries; risk provisioning; visible reserves; hidden reserves; Rücklage; Stille Reserve; Bank; Signalling; Eigenkapitalvorschriften; Asymmetrische Information; Betriebsgröße; Eigentümerstruktur; Deutschland